The Expression Patterns of Cytochrome Oxidase and Immediate-Early Genes Show Absence of Ocular Dominance Columns in the Striate Cortex of Squirrel Monkeys Following Monocular Inactivation - Li, Shuiyu; Yao, Songping; Zhou, Qiuying; Takahata, Toru (Frontiers in Neuroanatomy, 2021)
Because at least some squirrel monkeys lack ocular dominance columns (ODCs) in the striate cortex (V1) that are detectable by cytochrome oxidase (CO) histochemistry, the functional importance of ODCs on stereoscopic 3-D vision has been questioned. However, conventional CO histochemistry or trans-synaptic tracer study has limited capacity to reveal cortical functional architecture, whereas the expression of immediate-early genes (IEGs), c-FOS and ZIF268, is more directly responsive to neuronal activity of cortical neurons to demonstrate ocular dominance (OD)-related domains in V1 following monocular inactivation. Thus, we wondered what IEG expression would reveal in the squirrel monkey V1. In this study, we first examined CO histochemistry in V1 of five squirrel monkeys that were subjected to monocular enucleation or tetrodotoxin (TTX) treatment to address whether there is substantial cross-individual variation as reported previously. Then, we examined the IEG expression of the same V1 tissue to address whether OD-related domains are revealed. As a result, staining patterns of CO histochemistry were relatively homogeneous throughout layer 4 of V1. IEG expression was also moderate and homogeneous throughout layer 4 of V1 in all cases. On the other hand, the IEG expression was patchy in accordance with CO blobs outside layer 4, particularly in infragranular layers, although they may not directly represent OD clusters. Squirrel monkeys remain an exceptional species among anthropoid primates with regard to OD organization, and thus are potentially good subjects to study the development and function of ODCs.